Same-Sex Marriage: A Comparative Study of Indonesian, Netherlands, And American Legal Regulations and Their Socio-Legal Implications - Rahman, Muhammad Ridho; Rizani, Muhammad; Al Amruzi, M. Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
This research originates from the increasing global attention and public debate regarding same-sex marriage, which has sparked widespread controversy across various societies. The study seeks to provide a comparative analysis of the legal regulations on same-sex marriage in Indonesia, the Netherlands, and the United States, examining both their legal frameworks and the broader social implications that arise from them. Utilizing normative, comparative, and conceptual methodologies, the research investigates how each country approaches the issue based on its cultural norms, religious values, and constitutional commitments. In Indonesia, same-sex marriage remains unrecognized and is firmly rejected. The prevailing cultural and moral narratives in Indonesia reinforce the perception that marriage must be between a man and a woman, in accordance with religious teachings and traditional family structures. On the other hand, both the Netherlands and the United States have embraced stance by legalizing same-sex marriage. These countries view the issue through the lens of individual rights, equality before the law, and the protection of civil liberties. Their legal systems recognize same-sex unions as a fundamental expression of human dignity and freedom, aligning with broader commitments to human rights. The contrast between these legal approaches underscores how legal systems are profoundly shaped by a country's social context, ideology, and historical development. Therefore, the study highlights the importance of cultural relativism in law, emphasizing that legal interpretations and norms must be understood within the specific cultural and ideological contexts in which they exist.